PEMAHAMAN HADIS TAWASSUL: ANALISIS PRO-KONTRA TAWASSUL DENGAN DZAT SESEORANG - Eko Zulfikar; Beko Hendro (Jurnal Studi Hadis Nusantara, 2023)
This paper examines the pros and cons of opinions regarding the hadith regarding tawassul with one's essence. This paper uses a qualitative method. This paper concludes that opinions that are against tawassul to the essence of the pious and to the lovers of Allah, are considered the same as the attitude of disbelievers when worshiping idols which they consider an intermediary to Allah. Therefore, this counter group considers it an act of shirk and bid'ah. While the group that allows tawassul has many arguments that in general they have high respect for pious people. So the midpoint of these pros and cons, namely love for pious people, is appropriate, because through them Muslims can get to know religion, so that opinions that are against tawassul become refuted.